Reflective practice through video recording and journal writing-a case study - Samrajya Lakshmi, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The principal aim of this study is to examine how reflective practice enables ESL teachers to make sense of their professional worlds as well as make significant and worthwhile change within themselves and in their teaching practices. This paper presents analysis of the data gathered from the interviews, audio-video recordings, journal entries and post-reflection discussions. The data collected from the pre-reflection interviews indicate the subject’s beliefs about the teaching of English as a second language in general and specific aspects such as the classroom strategies and teaching aids. The data gathered from the video recordings and journal writings have been subjected to analysis to find emerging patterns and themes relevant to the participant teacher’s conceptualization of the use of reflective practice in his classroom.